Managing Postoperative Pain: The Role of Guided Imagery Therapy in Supravaginal Hysterectomy Patients with Uterine Myoma - Febriyanti, Hani; Septiyono, Eka Afdi; Kisnawati, Eni; Ulfia, Dina (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Myoma uteri are benign tumors that grow both inside and outside the uterus that are not malignant but can cause pain to those who have them. Management of uterine myoma is by surgery. Surgery is closely related to an incision in the skin, which can cause a feeling of pain in the patient. One of the non-pharmacology techniques that can be used to reduce the pain scale is guided imagery. Guided imagery is useful for increasing the relaxing effect, increasing comfort, and relieving the pain that is felt. This work aims to determine the analysis of guided imagery therapy to reduce postoperative pain of SVH (Supravaginal Hysterectomy) laparotomy. Implementation is carried out on patients. The method used in this study was a case study on a client with postoperative SVH laparotomy for indications of myoma uteri. Guided imagery therapy is carried out for 15-20 minutes, with pain assessment carried out before and after guided imagery is carried out. Pain scale measurement using a numeric rating scale (NRS). After being given guided imagery therapy the patient's pain scale which was initially 8 was reduced to 3. Image memory resulting from guided imagery can lead to the perception that the image is happening, which then affects pain receptors and can reduce the intensity of pain felt. Guided imagery relaxation therapy can reduce pain and anxiety and divert attention so that patients feel relaxed and happy.